Immunohistochemical study of CD147 and matrix metalloproteases in meningiomas: CD147 and matrix metalloproteases in meningiomas - Çinar, İlkay; Karagöz, Filiz (Journal of Surgery and Medicine, 2023)
Background/Aim: Expression of extracellular matrix proteins and metalloproteases (MMPs) has been implicated in neoplasm recurrence. Some recent studies have suggested a correlation between matrix modifier proteins and recurrence or invasion of meningiomas. Based on previous data, the aim of this study was to find a correlation between the immunohistochemical (IHC) expression patterns of a group of matrix modifier proteins, including CD147, Matrix Metalloprotease 2 and 9 (MMP2 and 9, respectively), Epithelial Cadherin (ECAD), and Galectin-3 (GAL3) with World Health Organization (WHO)-defined grade, brain invasion, recurrence, and other clinicopathological features. Methods: This study was a cohort study. All patients with meningioma who underwent resection over a 10-year period were identified from the electronic pathology archives. Tissue microarrays (TMAs) were created for IHC studies, and IHC staining was performed using standard methodology. Results: A total of 231 cases fulfilled the study criteria. Histological review identified 198 grade 1 tumors (85.3%), 28 grade 2 tumors (12.6%), and five grade 3 tumors (2.2%). CD147 was determined to be positively correlated with WHO-defined grade (P=0.009). ECAD, MMP2, MMP9, GAL3 were not found to be correlated with brain invasion, recurrence, or WHO grade. Conclusion: The study results demonstrated that CD147 could be a target for diagnosis, prognosis, and treatment of meningiomas.